2018
DOI: 10.3762/bjnano.9.35
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane juice derived carbon dot–graphitic carbon nitride composites for bisphenol A degradation under sunlight irradiation

Abstract: Carbon dots (CDs) and graphitic carbon nitride (g-C3N4) composites (CD/g-C3N4) were successfully synthesized by a hydrothermal method using urea and sugarcane juice as starting materials. The chemical composition, morphological structure and optical properties of the composites and CDs were characterized using various spectroscopic techniques as well as transmission electron microscopy. X-ray photoelectron spectroscopy (XPS) results revealed new signals for carbonyl and carboxyl groups originating from the CDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 77 publications
(88 reference statements)
1
10
0
Order By: Relevance
“…Recent results [8,10] also show that the luminescence of fresh porous silicon samples is subject to a large red shift when it is exposed to air and when the average size of the nanocrystals is smaller than 3 nm. On the other hand, recent luminescence measurements on silicon crystals obtained by silane decomposition are in good agreement with theory, but the luminescence is only observed for the largest crystallites.…”
Section: Results Of the Experimentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent results [8,10] also show that the luminescence of fresh porous silicon samples is subject to a large red shift when it is exposed to air and when the average size of the nanocrystals is smaller than 3 nm. On the other hand, recent luminescence measurements on silicon crystals obtained by silane decomposition are in good agreement with theory, but the luminescence is only observed for the largest crystallites.…”
Section: Results Of the Experimentsmentioning
confidence: 95%
“…The accelerated development of NTs is also associa ted with integrated semiconductor electronics -nanoelectronics (NE) and investigation of the nanoclusters [7,8]. The main principle here is to increase the level of integration by reducing the size of the active elements placed on the chip [9,10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common materials widely used include TiO 2 , ZnO, WO 3 , g-C 3 N 4 , etc. [6][7][8][9][10][11][12][249][250][251][252][253][254][255][256]. Photocatalysts have proven to be helpful in degrading several categories of organic contaminants including POPs and endocrine disrupting compounds (EDCs).…”
Section: Nanostructure Photocatalysts For Water and Wastewater Treatmentmentioning
confidence: 99%
“…Major categories of pollutants that have been successfully removed include textile dyes, phenolic compounds, pesticides, insecticides, aldehydes, pharmaceuticals, health care products, etc. It has been observed that intrinsic modifications such as doping, cocatalyst loading, as well as extrinsic modification such as addition of external electron acceptor can significantly enhance the mineralisation rate of these pollutants under diverse light sources [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…CQD could be easily produced and its properties could be modified with various functional groups by tuning the precursors and reaction parameters for different applications [ 11 ]. Previous studies showed that CQD had considerable promise in a variety of research areas such as biosensing, bioimaging and photocatalytic applications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%